The efficacy of multimodal intervention program on mental health states - Helena Baldonado Florendo; Joseph V. del Rosario (Intelektual Pustaka Media Utama, 2021)
Filipino youths are the hope of Philippine society. However, cigarette smoking and binge drinking continually corrupt this aspiration. Mental health states interplay with the growing setback of substance consumption. The main objective of the study is to determine the efficacy of the multimodal intervention program among the participants in this study. Specifically, it answers the following objectives: i) Develop an intervention program to address the high anxiety, mild depression, and normal self-esteem of the participants and ii) Determine the significant difference between the control group and the experimental group in the pre-test and post-test intervention measures. A matched-group experimental design was carried out among the participants who were randomly assigned to the control group and the experimental group. There were forty participants who met the criteria set by the researchers. When the multimodal intervention program was tested using t-test to analyze the findings at .05 level, it yielded significant results. Based on the findings of the study, the developed multimodal intervention program appeared to be effective. A follow-up study may be conducted to further test the efficacy.